Pengaruh dekomposisi Trichoderma virens pada berbagai jenis kompos kotoran ternak untuk menekan penyakit busuk pangkal batang bawang merah - Rosmini Rosmini; Nur Hayati; Burhanuddin Nasir; Flora Pasaru; Sri Anjar Lasmini (Fakultas Pertanian Universitas Yudharta Pasuruan, 2020)
Palu Valley shallot production is still very low namely 5.31 tonnes/ha when compared to national production which reaches 9.7 tonnes/ha, this is due to the attack of the base stem rot disease caused by Fusarium oxsyporum f.sp. cepae. This study aims to determine the effect of various types of organic fertilizer decomposed by Trichoderma virens on the incidence of stem rot disease and shallot yields. The research was conducted at the Laboratory of Pests and Plant Diseases, Faculty of Agriculture, Tadulako University, and shallot planting in Oloboju Village, Sigi Biromaru District, Sigi Regency, Central Sulawesi Province and lasted from March 2018 to August 2018. This research used a Randomized Block Design (RBD) with five treatments consisting of, without organic fertilizer (B0), cow manure 10 tons/ha + Trichoderma virens 100g/L (B1), chicken manure 10 tons/ha + T. virens 100g/L (B2), goat manure 10 tons/ha + T. virens 100g/L (B3), and petrogenic 5 tons/ha+ T. virens 100g/L (B4). The results showed that the use of 10 tons/ha cow manure decomposed by T. virens (B1) can reduce the intensity of stem rot disease on the Palu Valley shallot which is 5.61% to be 1.88% (3rd week) and 2.89% to be 0.98% (7th week), and increase shallot yield from 4.09 tons/ha to be 7.48 tons/ ha.